A Probabilistic-Based Method to Determine Optimum Size of Project Buffer in Construction Schedules - Romeo-Nunez, J (American Society of Civil Engineers, 2016)
Buffers are used to deal with the detrimental impacts of uncertainty on projects. However, methods for the allocation of buffers often provide single unique solutions, which are inefficient in the multiobjective decision-making environment of construction. This paper discusses a probabilistic-based buffer allocation method (PBAL), which enables the final decision on buffer size to be made by the project planners based on their preferences about project completion time. It investigates the construction projects where each activity starts as early as possible. Accordingly, the decision involves determining the size of time buffer at the end of the project network. The accuracy of the results is subjected to approximation and numerical errors in the mathematical models among others. Most buffer allocation heuristics for projects have approximation errors and simulation-based techniques introduce numerical errors by their iterative sampling calculation approach. PBAL can minimize these errors by supporting important details of modeling the production in activities, and preserving these details when modeling at the project level. The PBAL capability to minimize mathematical modeling errors and its accuracy has been successfully tested using the records from ten construction projects. © 2016 American Society of Civil Engineers.